Radiation immunodynamics in patients with glioblastoma receiving chemoradiation - Sloan, Lindsey; Sen, Rupashree; Liu, Chunnan; Doucet, Michele; Blosser, Lee; Katulis, Lisa; Kamson, David O.; Grossman, Stuart; Holdhoff, Matthias; Redmond, Kristin J.; Quon, Harry; Lim, Michael; et al. (Frontiers in Immunology, 2024)
This is a prospective, rigorous inquiry into the systemic immune effects of standard adjuvant chemoradiotherapy, for WHO grade 4, glioblastoma. The purpose is to identify peripheral immunologic effects never yet reported in key immune populations, including myeloid derived suppressor cells, which are critical to the immune suppressive environment of glioblastoma. We hypothesize that harmful immune-supportive white blood cells, myeloid derived suppressor cells, expand in response to conventionally fractionated radiotherapy with concurrent temozolomide, essentially promoting systemic immunity similar what is seen in chronic diseases like diabetes and heart disease. 16 patients were enrolled in a single-institution, observational, immune surveillance study where peripheral blood was collected and interrogated by flow cytometry and RNAseq. Tumor tissue from baseline assessment was analyzed with spatial proteomics to link peripheral blood findings to baseline tissue characteristics. We identified an increase in myeloid derived suppressor cells during the final week of a six-week treatment of chemoradiotherapy in peripheral blood of patients that were not alive at 2 years after diagnosis compared to those who were living. This was also associated with a decrease in CD8 + T lymphocytes that produced IFNγ, the potent anti-tumor cytokine. These data suggest that, as in chronic inflammatory disease, systemic immunity is impaired following delivery of adjuvant chemoradiotherapy. Finally, baseline investigation of myeloid cells within tumor tissue did not differ between survival groups, indicating immune surveillance of peripheral blood during adjuvant therapy may be a critical missing link to educate our understanding of the immune effects of standard of care therapy for glioblastoma.